Advanced light emissive materials for novel optical displays,lasers, waveguides, and amplifiers - Pîşkin, Serghei (D.Ghitu Institute of Electronic Engineering and Nanotechnologies, 2006)
The paper generalizes our results accumulated to the present time as well as it contains